2D spherulites of a semi-fluorinated alkane: controlled access to either radial or ring-banded morphologies - Liu, Xianhe; Mielke, Salomé; Tanaka, Motomu (ChemPhysChem, 2018)
Thin films of a semi-fluorinated alkane cast onto solid substrates consist of well-formed two-dimensional non-birefringent ring-banded and/or radial spherulites. Controlling the experimental conditions allows orientation of the crystallization toward either radial-only or ring-banded-only morphologies. Intermediate states were also captured in which both radial and ring-banded spherulites coexist. Monitoring of the formation of these intermediate states brought evidence for a first crystallization mode that sweeps radially outwards from a central nucleus until the propagating front edge experiences a second crystallization mode that proceeds through a diffusion-controlled rhythmic crystallization mechanism that leads to high (≈2 μm) concentric ridges. These 2D spherulites were investigated by optical and atomic force microscopies, interferometric profilometry, and off-specular neutron scattering.
Gesehen am 16.10.2018
First published: 23 October 2017